THE EFFECTIVENESS OF THE JOYFUL LEARNING-BASED TARGET METHOD IN IMPROVING BADMINTON SERVICE RESULTS - Wisnu Wardhana; Sapto Wibowo; Sugiharto Sugiharto; Sahabul Adri Ar; Didi Yudha Pranata (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2026)
Badminton service skill is a fundamental technique that requires accuracy, consistency, and active student engagement during the learning process. However, badminton learning in schools is still frequently dominated by repetitive instruction-based exercises that reduce students' motivation and participation. This study aimed to analyze the effectiveness of the joyful learning-based target method in improving students' badminton short service skills. This study employed a quantitative pre-experimental one-group post-test design. The population consisted of 105 tenth-grade students, with 70 students selected through simple random sampling. The intervention was conducted in 12 meetings using a target-based badminton service training integrated with joyful learning principles. The research instrument was a short service accuracy test consisting of 12 attempts with a scoring range of 1–5 for each trial. Instrument validity was confirmed through expert judgment, while reliability testing showed a high Intraclass Correlation Coefficient (ICC = 0.87). The data were analyzed using descriptive statistics and Cohen's d effect size analysis. The findings showed that 20% of students achieved the excellent category, 37% good, 26% fair, 13% poor, and 4% very poor. The mean score reached 41.8, which was classified as good. The intervention showed positive improvement in students' service accuracy and consistency. In addition, the effect size analysis indicated effectiveness at a moderate-to-high level (Cohen's d = 0.82). The joyful learning-based target method indicated effectiveness in improving badminton service skills and creating a more engaging learning environment in physical education.